Solvent extraction methods towards efficient recognition of organophosphorus pesticides: Recent progress and analytical challenges - Marzieh Fallahi Nezhad; Amin Foroozandeh; Hossein Salar Amoli; Mohammad Hasanzadeh (Talanta Open)
Dispersive Liquid–Liquid Microextraction (DLLME) has evolved significantly by integrating physical assistance methods to enhance extraction efficiency while minimizing the use of organic solvents and disperser agents. This review critically examines the latest advancements in assisted DLLME techniques, including ultrasound-assisted DLLME, vortex-assisted DLLME, and air-assisted DLLME methods, with an emphasis on their potential to minimize or eliminate the use of toxic organic solvents and disperser agents. These environmentally friendly approaches are particularly important for detecting hazardous contaminants such as organophosphorus pesticides (OPPs), which are widely used in agriculture and known for their acute neurotoxicity, environmental persistence, and potential to disrupt nervous systems. OPPs can cause severe neurological effects even at trace levels. Their continued presence in food, water, and environmental samples underscores the urgent need for highly sensitive and reliable detection methods to ensure public safety and regulatory compliance. The review highlights how greener DLLME techniques contribute to sustainable analytical practices by reducing or eliminating harmful chemicals. Comparative evaluations are presented for enrichment factors, extraction times, and analyte recoveries across various sample types, including environmental water, biological fluids, and food products. Finally, the review discusses future directions toward achieving completely solvent-free and disperser-free DLLME systems through innovative hybrid and energy-assisted strategies.